Stochastische Modellierung der Bildung von Nanopartikeln in reaktiven Strömungen - Schmitt, Manuel (KIT Scientific Publishing, 2017)
Soot formation in a laminar and a turbulent diffusion flame as well as the formation of iron oxide nanoparticles in an iron pentacarbonyl doped near stoichiometric H?/O?/Ar-premixed flame have been investigated numerically. The particular modus operandi of the simulated test cases is described. In the case of the turbulent flame the impact of the turbulent closure of the single particle source terms on particle size distribution is shown.